2022
DOI: 10.1155/2022/9292673
|View full text |Cite
|
Sign up to set email alerts
|

Recording of Falls in Elderly Fallers in Northern Greece and Evaluation of Aging Health-Related Factors and Environmental Safety Associated with Falls: A Cross-Sectional Study

Abstract: Background. Elderly falls constitute a global problem with huge social and economic aspects. Fall risk factors are both intrinsic (physical and psychological) and extrinsic (related with environmental safety). Aim. To record both intrinsic and extrinsic risk factors and their correlation in elderly fallers in order to suggest specific guidelines for their medical care and environmental modification inside and outside the home. Method. The study involved 150 elderly fallers (median age 70 (67-74)), who complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
1
19
0
4
Order By: Relevance
“…This is quite conceivable given that it can lead to disequilibrium and the old age person is often unable to rapidly regain his/her equilibrium and his/her physical fitness and abilities cannot help in preventing falling. Similar significant relations between dizziness and the risk of falling among elderly were reported in studies in Sweden ( 28 ) and Greece ( 29 ).…”
Section: Discussionsupporting
confidence: 83%
“…This is quite conceivable given that it can lead to disequilibrium and the old age person is often unable to rapidly regain his/her equilibrium and his/her physical fitness and abilities cannot help in preventing falling. Similar significant relations between dizziness and the risk of falling among elderly were reported in studies in Sweden ( 28 ) and Greece ( 29 ).…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, stairs or hallways increase the risk of falls in the elderly and accounted for 27.3% of all falls in this study [ 67 ]. Studies have shown that falling on the stairs can lead to the longest hospitalizations in the elderly [ 68 ]. This study also found that the falls while taking a bath or going to the toilet accounted for 10.5%, and the bathroom and toilet was one of the common injury locations [ 67 , 69 ]; here, environmental modification is able to reduce the fall rate [ 70 ], including adding handrails, increasing the spaciousness of passageways, and increasing lighting.…”
Section: Discussionmentioning
confidence: 99%
“…Falls also contribute to high healthcare costs for older adults. Falls are caused by several factors, both environmental as well as related to aging, making prevention strategies targeted at older adults a research focus [4,3] . Main causative factors of falls are the deficits in strength and balance of older adults because aging affects muscles, bones, joints, and the nervous system [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Falls are caused by several factors, both environmental as well as related to aging, making prevention strategies targeted at older adults a research focus [4,3] . Main causative factors of falls are the deficits in strength and balance of older adults because aging affects muscles, bones, joints, and the nervous system [4] . Exercise has been shown to help reduce these deficits by protecting older adults from experiencing another fall [2,5,6] .…”
Section: Introductionmentioning
confidence: 99%